Screening for cognitive impairment in an Australian aged care assessment team as part of comprehensive geriatric assessment. Issue 3 (4th May 2019) - Clarnette, Roger; Goh, Ming; Bharadwaj, Sneha; Ryan, Jillian; Ellis, Suzanne; Svendrovski, Anton; Molloy, D. William; O'Caoimh, Rónán
ABSTRACT: Accurate detection of mild cognitive impairment (MCI) is important to stratify and address risk. Yet, few short cognitive screening instruments are validated for this. . In Australia, all clients referred to an Aged Care Assessment Team (ACAT) receive comprehensive geriatric assessment (CGA) including the Standardized Mini-Mental State Examination (SMMSE). We compared the accuracy of the quick mild cognitive impairment (Q mci ) screen to the SMMSE in 283 participants: 195 with dementia, 47 with MCI, and 41 with subjective cognitive decline (SCD) in an Australian community-based ACAT. Both had similar accuracy in identifying dementia, AUC of 0.86 for the Q mci versus 0.93 for the SMMSE ( p  = 0.10), but the Q mci was more accurate than the SMMSE in differentiating MCI from SCD, AUC of 0.84 versus 0.71, respectively, p  = 0.046. These suggest that the new, short (3–5 min) Q mci screenis appropriate for use in an ACAT or other units conducting CGA.